2013
DOI: 10.1016/j.exppara.2012.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Trichomonas vaginalis activity of marine-associated fungi from the South Brazilian Coast

Abstract: Trichomonas vaginalis is the causative agent of trichomonosis, the most common non-viral sexually transmitted disease. Infection with this protozoan may have serious consequences, especially for women. Currently, 5-nitroimidazole drugs are the treatment of choice for trichomonosis, but the emergence of resistance has limited the effectiveness of this therapy. In this context, this study aimed to evaluate the anti-T. vaginalis activity of marine-associated fungi found in the South Brazilian Coast. A total of 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…T. vaginalis is a flagellated parasite affecting about 156 million people each year in the world [32]. Trichomoniasis infection may cause serious health consequences, especially for women [33]. The current treatment is being based upon 5-nitroimidazole [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T. vaginalis is a flagellated parasite affecting about 156 million people each year in the world [32]. Trichomoniasis infection may cause serious health consequences, especially for women [33]. The current treatment is being based upon 5-nitroimidazole [33].…”
Section: Discussionmentioning
confidence: 99%
“…Trichomoniasis infection may cause serious health consequences, especially for women [33]. The current treatment is being based upon 5-nitroimidazole [33]. However, the emergence of resistance has limited the effectiveness of this therapy [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Scopel et al [ 129 ] isolated two sponge-associated fungi, namely Hypocrea lixii F02 and Penicillium citrinum F40 ( Table 4 ) that were active against the protozoal parasite Trichomonas vaginalis , which causes trichomoniasis, a sexually transmitted disease [ 130 ]. Culture filtrates of both isolates inhibited T. vaginalis ATCC 30236 and fresh clinical isolates, including the metronidazole-resistant TV-LACM2, with MIC values of 2.5 mg/mL.…”
Section: Antiprotozoal Activitymentioning
confidence: 99%
“…Culture filtrates of both isolates inhibited T. vaginalis ATCC 30236 and fresh clinical isolates, including the metronidazole-resistant TV-LACM2, with MIC values of 2.5 mg/mL. Further observation indicated that culture filtrates of these two fungi had no haemolytic effect against mammalian cells, which is one of the important criteria to further develop anti-protozoal drugs [ 129 ].…”
Section: Antiprotozoal Activitymentioning
confidence: 99%
“…Several research groups around the world have paid attention to discover natural products from marine organisms with activity against protozoal diseases, such as malaria, Chagas disease, leishmaniasis, and African trypanosomosis [11 -13]. Anti-Trichomonas activity was also described in studies on marine algae [14 -16] and fungi [17]. Extracts from twenty-five seaweeds were tested against T. vaginalis, of which 44% presented high to moderate activity with low cytotoxicity [14].…”
Section: Introductionmentioning
confidence: 99%